Heat transfer enhancement by carbon nanostructure based nanofluids in an annular heat exchanger / Hamed Khajeh Arzani - Hamed Khajeh, Arzani (2016)
Present thesis work introduces a new design of heat exchangers utilizing an annular profile which opens a new gateway for realizing optimization of higher energy transfer. To apprehend this goal, nanofluids have been studied for this application as it has got thermal conductivity higher than conventional liquids. In this study, a cooling loop apparatus was designed and built to evaluate the transition and turbulent heat transfer performance of water and ethylene glycol based nanofluids. Also numerical simulation was employed as an approximating procedure for prediction of the results in this study. Two-phase mixture model has been considered for simulation of the nanofluids flow in two and three dimensional annular heat exchanger. Graphene Nanoplatelets (GNP) were stably dispersed in aqueous media by covalent and non-covalent functionalization. At a constant concentration, the measurement has shown that the thermal conductivity of covalent nanofluid (GNP-COOH/water) is higher than the non-covalent nanofluid (GNP-SDBS/water), which is higher than distilled water. In the second phase of the study, multi-walled carbon nanotubes (MWCNT) has been covalently functionalized with Aspartic acid (Asp) to achieve a highly dispersed colloidal suspension of MWCNT. After investigation of stability of colloidal suspensions with Uv-vis spectroscopy, the prepared coolants have the promising properties such as high thermal conductivity as compared with water. Forced convection heat transfer coefficient and pressure drop were also investigated at three different heat fluxes and four weight concentrations. The observed high heat transfer rate, poor change in the pressure drop in the presence of different weight concentrations provided a suitable condition for this novel alternative coolant. In the third phase of study, the improvement of colloidal stability of Graphene Nanoplatelets (GNP) in aqueous media has been implemented by functionalization with tetrahydrofurfuryl polyethylene glycol in a quick electrophonic addition reaction method. To address this issue, surface functionalization of GNP was analyzed by Raman spectroscopy, and thermogravimetric analysis. In addition, the morphology of treated samples was investigated by transmission electron microscopy (TEM). The steady-state forced convective heat transfer experiments and the simulation results confirmed the promising cooling capabilities of the TGNP/water. The last phase is related to the thermophysical and heat transfer performance of covalently functionalized GNP-based water/ethylene glycol nanofluid in an annular channel. After experimentally measuring thermophysical properties of the prepared samples, a computational fluid dynamics study has been carried out to study the heat transfer and pressure drop of well-dispersed and stabilized nanofluids. Based on the results of this investigation, there is a significant enhancement on the heat transfer rate associated with the loading of well-dispersed GNP in basefluid.